Project System, un modelo de gestión para construir el desarrollo sostenible - Dejo, Federico (2007)
This paper shows the advantages of the Scorecard Project System as a computer integrated tool to simplify, speed up and streamline the design and monitoring of diagnosis studies, plans and projects included in a strategic view to reach sustainable development. The paper shows the characteristics and advantages of each such tool and establishes their sequence in the feedback cycle for territorial management, whether peasant communities, local governments, regional governments of companies with a social responsibility mission.